The Role Of Customer Experience In Enhancing Customer Satisfaction And Loyalty On The Shopee Platform - Nadita, Nadya (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines how Customer Experience influences customer satisfaction and ultimately strengthens customer loyalty on the Shopee platform in Indonesia. The research is motivated by the growing competition in e-commerce, evolving consumer behavior, and challenges in maintaining trust and satisfaction, which are critical for sustaining loyalty. Background Problems: The research seeks to answer: Does Customer Experience significantly affect customer satisfaction and loyalty, and how do related factors such as trust and digital service quality contribute to these relationships? Research Methods: A quantitative descriptive approach was employed using purposive sampling. Data were collected through questionnaires distributed to 100 active Shopee users who had made at least one transaction in the past six months. Path analysis was applied to examine the relationships among Customer Experience, satisfaction, loyalty, and trust. Finding/Results: The findings reveal that Customer Experience has a positive and significant impact on Customer Satisfaction, which in turn positively influences Customer Loyalty. E-service quality also significantly affects loyalty, while trust directly impacts loyalty without mediation by satisfaction. Digital interactions—such as communication, feedback, and algorithm-driven personalization—play a role in enhancing satisfaction and building trust. Conclusion: The study concludes that Customer Experience is a key determinant of satisfaction and loyalty among Shopee users. The practical implication is that Shopee should adopt a holistic approach to improving digital customer experience to maintain loyalty in an increasingly competitive e-commerce environment. Future research should explore the moderating role of personalization and technological innovation in shaping customer loyalty.